Residual Effect of Silicate Agromineral Application on Soil Acidity, Mineral Availability, and Soybean Anatomy - de Carvalho Ribeiro, Mariana [UNESP]; Ganga, Antonio; Cattanio, Isabella Silva [UNESP]; Martins, Aline Redondo [UNESP]; Alves, Rodrigo Silva [UNESP]; Lessa, Luís Gustavo Frediani [UNESP]; Pereira, Hamilton Seron; Galindo, Fernando Shintate [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Abreu-Junior, Cassio Hamilton; Capra, Gian Franco; Jani, Arun Dilipkumar; et al. (MDPI, 2025)
Silicate agrominerals (SA) may be sustainable soil amendments that can minimize dependence on conventional fertilizers (CF). We evaluated the residual effects of SA application as a source of Si and as a soil remineralizer, using soils with contrasting chemical-physical features cultivated with soybean. The experiment was conducted under greenhouse conditions and treatments were arranged in a 5 × 2 + 2 factorial scheme: five rates of SA, two soils in addition to CF. The soil was incubated before cultivation, followed by the sequential sowing of corn and soybean. At the R4 phenological stage, when the pods were fully developed, soybean plants were harvested for anatomical leaf tissue analysis and P, Ca, Mg, and Si accumulation. After harvest, the soil was analyzed. Application of SA rates reduced potential acidity (H + Al) and exchangeable acidity (Al3+) and increased soil pH, sum of bases (SB), cation-exchange capacity (CEC), and base saturation (BS), in addition to promoting the nutrient’s availability and Si. Stomatal density was higher on the adaxial face of plants cultivated in the medium-textured soil. Silicate agrominerals can be used as a soil acidity corrector and remineralizer, improving the root environment and increasing the availability of nutrients and silicon.
Keywords: Glycine maxL; remineralizers; rock dusting; silicon; sustainable agriculture